Forest amount determines the occupancy of the arboreal rodent Oecomys cleberi (Rodentia: Cricetidae) in Atlantic Forest fragmented landscapes - Brito Dias, Viviane [UNESP]; Martello, Felipe; Regolin, André Luis; Tomas, Walfrido Moraes; Ribeiro, Milton Cezar [UNESP] (Taylor & Francis, 2023)
Oecomys cleberi is an arboreal rodent little known reagarding its natural history, distribution, and ecology. In this paper, we present new records of O. cleberi within a region of the Atlantic Forest, in a transition zone with Cerrado, in the northwestern state of São Paulo. We investigated the effects of the structure of fragmented landscapes on its occurrence at 40 sites in this region. We detected O. cleberi only in seasonal semideciduous forests and palm forests, but not in pastures, wetlands, and young reforestation. Our results indicated that its occurrence was determined by the amount of habitat within a 500 m radius landscape, and extremely low occupancy probabilities in landscapes with less than 25% forest cover (ψ < 0.3). Our results show the importance of the amount of habitat at the landscape scale for the occurrence of Oecomys cleberi, and point out that most of the landscapes in the study region presented low occupancy probabilities by this forest rodent. Although O. cleberi should not be considered as an Atlantic Forest species, it seems to be a resident species in ecotone areas with Cerrado, within the Atlantic Forest domain. Thus, conservation actions are necessary to preserve their populations in these regions.
Keywords: Cleber’s Arboreal Rice Rat; conservation units; fragmentation; occupancy modeling; small mammals